USING COMMUNICATIVE ACTIVITIES TO TEACH ENGLISH PROSODY IN EFL CLASSROOMS - Durova Shaxnoza Shokirovna (Ethiopian International Journal of Multidisciplinary Research, 2026)
Prosody, which includes stress, rhythm, and intonation, plays a crucial role in effective communication in English. However, in many English as a Foreign Language (EFL) classrooms, pronunciation teaching often focuses primarily on individual sounds rather than suprasegmental features. This article explores the effectiveness of communicative activities in teaching English prosody to EFL learners. The study highlights how interactive classroom tasks such as role-plays, dialogues, storytelling, and information-gap activities can improve learners’ awareness and use of prosodic features. The research is based on classroom observations and practical teaching experience with university-level EFL students. The findings suggest that communicative activities significantly enhance students’ pronunciation accuracy, fluency, and listening comprehension. The study concludes that integrating communicative techniques into pronunciation teaching can make prosody instruction more engaging and effective for language learners.